DRUG THERAPY FOR PROTEIN COMPOSITION CHANGES OF BLOOD IN HYPERTENSION AND IN CASES OF COMORBIDITY - Dzordzo, Yu. R.; Andreychyn, S. M. (International Journal of Medicine and Medical Research, 2022)
Background. The binding function of serum albumin (BFSA) and its changes in various diseases in recent years are of interest to researchers. Hypertension (HT) in combination with comorbidities, including non-alcoholic steatohepatitis (NASH) and type 2 diabetes mellitus (DM) can contribute to BFSA. Objective. The aim of this study is to evaluate the relationship between quantitative changes in BFSA, protein fractions and indicators of endogenous intoxication (EI) in HT in combination with NASH and type 2 diabetes and to suggest drug therapy of the disorders revealed. Methods. 123 patients with stage 2 HT and degree 2-3 arterial hypertension were examined; they were divided into three groups: group 1 included 28 patients without concomitant diseases, 2 – 48 patients with concomitant NASH, 3 – 47 patients with NASH and type 2 diabetes. Groups 3 and 4 were divided into two subgroups (A and B): patients of the subgroup A received basic HT therapy and additionally Antral® 200 mg 3 times a day for 60 days, B – only basic HT therapy. All patients underwent a standard clinical examination, as well as for BFSA, total protein, albumin, globulins and albumin-globulin ratio, medium mass molecules (MMM) at 280 and 254 nm and erythrocyte intoxication index (EII). The comparison group consisted of 25 healthy individuals. Results. It was found out that Antral® in patients with HT in combination with NASH and with NASH and type 2 diabetes with a statistically significant decrease in BFSA, total protein and albumin, as well as with increased indicators of EI (MSM254, MSM280 and EII) caused significant improvement in BFSA, increase of total protein, serum albumin, reduce of MSM254, MSM280, EII and strengthening of all correlations. Conclusions. Antral® therapy in patients with HT in combination with NASH as well as NASH and type 2 diabetes causes significant increase in BFSA, serum protein fractions and decreases EI.